Pengembangan Media Auto Play Pada Materi Struktur bagian Tumbuhan Dalam Meningkatkan Hasil Belajar Siswa di Sekolah Dasar Kabupaten Probolinggo - Sriwijayanti, Ribut Prastiwi; Qomariah, Rysca Siti; Shohibuddin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
Learning media has a very important role in the learning process, through the learning media student will be easier to understand the material presented. So also in the science lessons especially material of Structures Plant which during the learning is monotonous. Therefore, Researchers developed a product of learning media in the form Autoplay which is able to present the material in a concrete way for students, the presentation of the material in this learning media accompanied by pictures, animations and videos that make learning media more interesting and motivate for students to learn. The goals of this research development is knowing the product design of learning media based on autoplay, knowing the level of validity and attractiveness of the product of learning media based on autoplay, and knowing the difference understanding of the concept of control class with experiment class that using learning media based on autoplay. The method using in this reserach is research and development with BORG AND GALL model of development. The procedure of development in this research are adapted from development of BORG AND GALL to be four steps they are preliminary step,development step, validation and revision and trying in field step. This research was conducted in SDI Tarbiyah with the subject of the trial as many as 18 students of class IV. Results of the development of this media is the product of media development of this in the form learning media by using a software program Autoplay Studio 8 that the material is accompanied by pictures of related material, video animation using software of flash player associated with learning, and quizzes smart application uses Quiz creator. The validation of development product can be seen from the sheet validation from validator of experts consisting of design experts with a percentage of 95% (very valid), Experts of material/content with a percentage 82% (valid) and teachers of science with 89% (very valid), whereas the level of attractiveness of the media can be seen from the questionnaire students of class IV with a percentage of 93% (very valid). The average acquisition value of last Post-Test was reached 90.56 compared to Pre-Test reached 78.33. DOI: https://doi.org/10.33399/edukasia.v2i1.28